Psycho-Neuroendocrine-Immune Interactions in COVID-19: Potential Impacts on Mental Health - Raony, Ícaro; de Figueiredo, Camila Saggioro; Pandolfo, Pablo; Giestal-de-Araujo, Elizabeth; Oliveira-Silva Bomfim, Priscilla; Savino, Wilson (Frontiers in Immunology, 2020)
Coronavirus disease 2019 (COVID-19) is caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The impacts of the disease may be beyond the respiratory system, also affecting mental health. Several factors may be involved in the association between COVID-19 and psychiatric outcomes, such as fear inherent in the pandemic, adverse effects of treatments, as well as financial stress and social isolation. Herein we discuss the growing evidence suggesting that the relationship between SARS-CoV-2 and host may also trigger changes in brain and behavior. Based on the similarity of SARS-CoV-2 with other coronaviruses, it is conceivable that changes in endocrine and immune response in the periphery or in the central nervous system may be involved in the association between SARS-CoV-2 infection and impaired mental health. This is likely to be further enhanced, since millions of people worldwide are isolated in quarantine to minimize the transmission of SARS-CoV-2 and social isolation can also lead to neuroendocrine-immune changes. Accordingly, we highlight here the hypothesis that neuroendocrine-immune interactions may be involved in negative impacts of SARS-CoV-2 infection and social isolation on psychiatric issues.